2018
DOI: 10.4018/978-1-5225-2709-1.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of The Uniaxial Compressive Strength of Rocks Materials

Abstract: This study briefly will review determining UCS including direct and indirect methods including regression model soft computing techniques such as fuzzy interface system (FIS), artifical neural network (ANN) and least sqeares support vector machine (LS-SVM). These has advantages and disadvantages of these methods were discussed in term predicting UCS of rock material. In addition, the applicability and capability of non-linear regression, FIS, ANN and LS-SVM SVM models for predicting the UCS of the magnatic roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 227 publications
1
3
0
Order By: Relevance
“…This is an advanced version that is superior to the artificial neural networks method in terms of predictive performance, generality, and robustness. This is consistent with the research of [29] who investigated the advantages and disadvantages of fuzzy inference systems, artificial neural networks and LS -SVM methods and found that the performance of the LS -SVM model was the best among the other methods. However, the small difference in R 2 between the models in this paper and [31] shows the similarity of the success of both models and does not imply that the Bagging model is less useful or less accurate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is an advanced version that is superior to the artificial neural networks method in terms of predictive performance, generality, and robustness. This is consistent with the research of [29] who investigated the advantages and disadvantages of fuzzy inference systems, artificial neural networks and LS -SVM methods and found that the performance of the LS -SVM model was the best among the other methods. However, the small difference in R 2 between the models in this paper and [31] shows the similarity of the success of both models and does not imply that the Bagging model is less useful or less accurate.…”
Section: Discussionsupporting
confidence: 91%
“…Random forest modelling is increasingly used for a variety of purposes [16], and can also be used as a variant of a regression tree to estimate the uniaxial compression strength for mudstone and wackestone carbonates [17] and sandstones [18]. When it comes to elastic modulus, simple regression equations [19][20][21][22][23][24] have been mostly used for its estimation, followed by multiple regression equations [25][26][27], neural networks [28], and other modern platforms for estimation are used with them [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the SVR model was more accurate than the other models. Ceryan et al (2018) used various ML models, namely, FIS (fuzzy inference system), ANN, and LV-SVM. So, the LV-SVM model was the best in predicting UCS.…”
Section: Related Workmentioning
confidence: 99%
“…Ceryan et al developed the fuzzy interface system (FIS), ANN, and LV-SVM to predict the UCS of rocks. According to their results, LV-SVM performed better than the other developed models [34]. Neurogenetic and multiple regression (MR) methods were developed by Monjezi et al to estimate the UCS of rocks.…”
Section: Introductionmentioning
confidence: 99%